2015
DOI: 10.1007/s00520-015-2977-1
|View full text |Cite
|
Sign up to set email alerts
|

Cancer rehabilitation and palliative care—two important parts of comprehensive cancer care

Abstract: In this issue of Supportive Care in Cancer, Julie K. Silver et al. focus on cancer rehabilitation and palliative care delineating their respective roles in comprehensive oncology care [1]. The authors describe how cancer rehabilitation and palliative care are quite similar in goal setting, namely to improve physical, cognitive, psychological, and social aspects of quality of life in cancer patients-both specialties prioritizing goalconcordant care through identification of patient and family preferences and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…As survival rates are increasing, cancer rehabilitation is an important part in the treatment and care of cancer patients [1,2]. With this "Special", we aim to give an insight in the Austrian situation of cancer rehabilitation, and furthermore to highlight the importance of the field of Physical Medicine and Rehabilitationwith competencies in diagnostic and therapy as well as of coordination of the multi-professional and interdisciplinary rehabilitation teams for cancer rehabilitation [2].…”
Section: Aspects Of Cancer Rehabilitation: An Austrian Perspectivementioning
confidence: 99%
“…As survival rates are increasing, cancer rehabilitation is an important part in the treatment and care of cancer patients [1,2]. With this "Special", we aim to give an insight in the Austrian situation of cancer rehabilitation, and furthermore to highlight the importance of the field of Physical Medicine and Rehabilitationwith competencies in diagnostic and therapy as well as of coordination of the multi-professional and interdisciplinary rehabilitation teams for cancer rehabilitation [2].…”
Section: Aspects Of Cancer Rehabilitation: An Austrian Perspectivementioning
confidence: 99%
“…While cancer patients are living longer, many have resultant physical and cognitive disabilities, which may impair their quality of life. Indeed, studies have shown a high prevalence of functional impairments among cancer patients with a wide range of diagnoses and treatment situations [2][3][4][5][6][7]. In an effort to improve the quality of life of cancer survivors, increasing attention has been given to improving functional recovery following treatment.…”
Section: Introductionmentioning
confidence: 99%
“…At the Comprehensive Cancer Centre (CCC) of the Medical University of Vienna (General Hospital of Vienna, Austria), we have a so-called CCC-platform for Side effectsManagement, Supportive Care & Rehabilitation (CCC-SMSCR) which is able to help patients to handle various barriers such as functional deficits, symptoms, and emotional distress [6]. Furthermore, this CCC-platform aims Bto increase knowledge^, Bto inform and to network^and Bto improve quality of treatment and care^at the moment especially including aspects of sports, workability, employment and return to work [7,8].…”
mentioning
confidence: 99%